Chemical Synthesis of the Sec-To-Cys Homologue of Human Selenoprotein F and Elucidation of Its Disulfide-pairing Mode - Liao, Peisi; He, Chunmao (Frontiers in Chemistry, 2021)
Herein, we document a highly optimized synthesis of the Sec-to-Cys homologue of the human selenoprotein F (SelF) through a three-segment two-ligation semisynthesis strategy. Highlighted in this synthetic route are two one-pot manipulations, i.e. the first ligation followed by a desulfurization and the second ligation followed by the protein refolding. This way multi-milligrams of the folded synthetic protein was obtained, which set the stage for the synthesis of the natural selenoprotein. Moreover, the disulfide pairing mode of the SelF was elucidated through a combination of site-directed mutagenesis and LC-MS study. It provides not only a criterion to judge the viability of the synthetic protein, and more importantly, useful structural insights into the previously unresolved UGGT-binding domain of SelF.